Mechanistic reasoning of selected form four science students on the theory of cell / Lee Shuh Shing - Lee, Shuh Shing (2013)
Understanding the causal mechanisms that underlie natural phenomena is the focus of biological inquiry. Mechanistic reasoning is a thought process as to how a cause brings about an effect. Without this skill, students find it hard to explain various biological processes, for example such as those related to cells. However, research has shown that many teachers believe that it is inappropriate in trying to infuse mechanistic reasoning among the low achieving students as compared to the high achieving ones. Thus, the overall aim of this study was to explore in depth, selected Form Four high and low achieving students’ mechanistic reasoning for the Theory of Cell. In addition, the study investigated students’ progression of mechanistic reasoning as well as the emergent representations or the learning outcomes of their mechanistic reasoning. This study is an exploratory study which employed qualitative data collection methods. The study began with the preparation of three instruments which were the Science Test, the Incoherency Tests and the Living Cell Tool. The Science test was used to categorise students into high and low achievers. Based on the Science Test, four highachieving and six low achieving students were identified as the sample of this study. The four incoherency tests were used to explore students’ incoherencies for the four chapters related to the Theory of Cell in order to prepare the Living Cell Tool. The Living Cell Tool was prepared both as a teaching-learning material to infuse mechanistic reasoning as well as a tool to collect data. Since the Living Cell Tool was utilised in a normal classroom lesson, it was prepared aligned with the Form Four Biology curriculum specified by the Ministry of Education. Infusion of mechanistic reasoning was carried out over five months for the four topics related to the Theory of Cell which were cell structure and organisation, movement of substances across the plasma membrane, chemical composition of cell and iv cell division. Data was obtained from students’ written answers, researcher’s observations, audio and video data reflecting students’ mechanistic reasoning, and students’ interviews. Due to the complexity of the data, using existing analytical frameworks was insufficient to uncover in depth the students’ mechanistic reasoning. Thus, the researcher through much discussion planned a seven (7) step procedure to analyse students’ mechanistic reasoning. This procedure revealed four types of cognitive processing within the mechanistic reasoning among the student sample. There were named as Type I and Type II Simple Cognitive Processing and Type I and Type II Complex Cognitive Processing in ascending order. The findings showed that in the beginning of this study all of the high and low achieving students only managed to achieve either Type I or Type II simple cognitive processing. Furthermore, as the study proceeded, both the high and low achieving students’ mechanistic reasoning began to achieve Type I or Type II complex cognitive processing. Upon further analysis, the study also revealed several learning outcomes which were named as representations as a result of the students’ mechanistic reasoning. These representations reflected the students’ understanding of the Theory of cell and were categorised as intuitive representations, assimilated representations, transformational representations and misinterpreted representations. Implications and suggestions for further research were also put forward.